Effects of long-term growth hormone therapy in a girl with Floating-Harbor syndrome - Hyun Woo Son; Jeong Eun Lee; Seung Hwan Oh; Changwon Keum; Woo Yeong Chung (Korean Society of Pediatric Endocrinology, 2020)
Floating-Harbor syndrome is a rare autosomal dominant disorder that presents with short stature, facial dysmorphism, significantly delayed bone age, skeletal abnormalities, speech and language problems, and intellectual disabilities. Although short stature is one of the main clinical manifestations, use of growth hormone therapy in Floating-Harbor syndrome patients has been limited. Only a few reports have investigated the response to growth hormone therapy with regard to final adult height. We report the case of a 7-year-old girl with FloatingHarbor syndrome and a heterozygous mutation, c.7330C > T (p.Arg2444*), in the SRCAP gene. The patient exhibited dysmorphic facial features, severe intellectual disabilities, obsessive-compulsive and aggressive behaviors, and short stature without growth hormone deficiency. Her height standard deviation score improved after 55 months of growth hormone therapy.